DEVELOPING SPEAKING SKILL THROUGH ROLE PLAY ACTIVITIES - Ade Hidayat (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
This study aims to investigate the implementation of role play activities in developing students’ speaking skill and how it affects students’ enthusiasm during the language learning process. It is designed as classroom action research with 32 first year senior high school students as the research subjects. Data for the research was collected in two cycles during the research through speaking test and observation checklist. It is found that the implementation of role play activities can improve students’ speaking skill where the students also found the learning process to be challenging and fun. It also indicates that the implementation of role play activities for teaching speaking has positive impact on students’ motivation as shown in the result where the majority of the students were active and enthusiast during the classroom learning process.